Gender and sociocultural factors in animal source foods (ASFs) access and consumption in lower-income households in urban informal settings of Nairobi, Kenya - Bukachi, Salome A.; Ngutu, Mariah; Muthiru, Ann W.; Lépine, Aurélia; Kadiyala, Suneetha; Domínguez-Salas, Paula (Springer, 2022)
Background Gender shapes household decision-making and access for nutritious diets, including animal source foods (ASFs) that impact on child health and nutrition status. However, research shows that the poorest households in the urban informal settlements of Nairobi have low ASFs consumption. This study was conducted to explore further from a qualitative perspective the gender, sociocultural factors affecting household ASF consumption this study.